Influence of Ceramic Roof Tile Waste Powder Fineness on Slump Loss and Water Content of Concrete with Cement Substitution - Imam Wibowo; Nor Intang Setyo Hermanto; Agus Maryoto (Jurnal Ilmiah Dinamika Rekayasa, 2026)
The annual production of defective ceramic roof tile waste is estimated at around 15,262 tons yet remains underutilized. Previous studies reported that substituting cement with ceramic roof tile powder finer than cement does not significantly enhance mortar compressive strength. Furthermore, the effect of waste powder exceeding cement fineness on fresh concrete performance has not been sufficiently investigated. Therefore, this study examined the effect of ultra-fine ceramic roof tile waste powder (CRTWP) as a partial cement replacement on concrete slump loss behavior and water demand. The tile waste was ground to achieve fineness higher than cement using the Blaine air permeability method. Slump loss tests were conducted using an Abrams cone on concrete mixtures with CRTWP substitution levels of 0%, 2.5%, 5%, 7.5%, and 10% by weight of cement, with initial slump values maintained constant. The results revealed that incorporating ultra-fine CRTWP produced similar final slump loss values, despite differences in required mixing water. Higher water content signified better workability retention and slower early-stage stiffening. These results implied that ultra-fine CRTWP could be used as a partial cement substitute without adversely affecting fresh concrete workability, provided appropriate water adjustments are implemented.